A DISCOURSE ANALYSIS ON STUDENT TALKS IN EFL CLASSROOM INTERACTION - Wahyu Wahyu (Institut Agama Islam Negeri (IAIN) Bone, 2022)
This research aimed to discover the formal and informal talks of the students in EFL classroom. This research was conducted in qualitative design. Furthermore, the researcher applied discourse analysis under the study of sociolinguistics as an approach to analyze the language, writing, speech, and conversation (verbal and nonverbal) that was appropriate with the purpose of this research. In order to get the data, the researcher did observation, recording. Lastly, the result of the data analysis was presented in description of words, not number. The research was conducted at the first and fifth semester groups of English Study Program of IAIN Bone. The result shows that the students used formal and informal language. The informal talks which occurred in EFL classroom particularly in student talks were colloquial lexis, interruption/overlapping, first name and nickname, typical mood choice and modal for probability. Most of the informal talks uttered by the students were included as new characteristic of informal language that was in form of regional term.Keywords: EFL Classroom; Formal and Informal talks; Student talks